2019
DOI: 10.1177/0897190019869158
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Polypharmacy in Rheumatoid Arthritis—A Challenge Not Covered by Current Management Recommendations: Data From a Large Real-Life Study

Abstract: Background: Rheumatoid arthritis (RA) is associated with high frequency of comorbidities and increased risk of polypharmacy. Although there is a great potential for complications, there is a gap in literature on polypharmacy in patients with rheumatic arthritis. Objective: To evaluate the prevalence and factors associated with polypharmacy in a population in a real-life setting. Methods: A cross-sectional multicenter study was conducted in Brazil. Patients underwent clinical evaluation and medical records anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
(84 reference statements)
1
14
0
Order By: Relevance
“…This observational study shows polypharmacy (defined as ≥5 medications) in 33.7% of RA-patients, especially in female patients older than 50 years. This number is low in comparison with current literature, reporting polypharmacy in as many as 44.4 to 67.9% of all RA-patients (19,21,22). The reason for this difference may be differences of the insurance systems, or the fact that definitions used for polypharmacy are still not consistent (2, 6).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…This observational study shows polypharmacy (defined as ≥5 medications) in 33.7% of RA-patients, especially in female patients older than 50 years. This number is low in comparison with current literature, reporting polypharmacy in as many as 44.4 to 67.9% of all RA-patients (19,21,22). The reason for this difference may be differences of the insurance systems, or the fact that definitions used for polypharmacy are still not consistent (2, 6).…”
Section: Discussionmentioning
confidence: 63%
“…The reason for this difference may be differences of the insurance systems, or the fact that definitions used for polypharmacy are still not consistent (2, 6). In the systematic literature review, the definition of more than 5 drugs was applied in one trial (22), the definitions of more than 3 drugs in another one (6), while all other studies did not provide a specific definition used. In order to make observations and documentations more comparable throughout the literature, a consensus will be helpful for the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in rheumatoid arthritis cohorts show that patients with rheumatoid arthritis tend to have polypharmacy (median number of drugs approximately 5) and, further, that older age tends to increase the risk for polypharmacy (65,66). Other studies have also shown polypharmacy to be a predictor of adverse outcomes in rheumatoid arthritis (67).…”
Section: Discussionmentioning
confidence: 99%